2021
DOI: 10.3390/pathogens10040400
|View full text |Cite
|
Sign up to set email alerts
|

La Crosse Virus Shows Strain-Specific Differences in Pathogenesis

Abstract: La Crosse virus (LACV) is the leading cause of pediatric viral encephalitis in North America, and is an important public health pathogen. Historically, studies involving LACV pathogenesis have focused on lineage I strains, but no former work has explored the pathogenesis between or within lineages. Given the absence of LACV disease in endemic regions where a robust entomological risk exists, we hypothesize that some LACV strains are attenuated and demonstrate reduced neuroinvasiveness. Herein, we compared four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Dulbecco's Modified Eagle Media (DMEM) containing 2% Fetal Bovine Serum (FBS), 100 units of Penicillin and 0.1 mg Streptomycin), for virus quantification by plaque assay. Mice were immediately euthanized when moribund or upon weight loss greater than or equal to 20% of their original body weight, as previously described [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Dulbecco's Modified Eagle Media (DMEM) containing 2% Fetal Bovine Serum (FBS), 100 units of Penicillin and 0.1 mg Streptomycin), for virus quantification by plaque assay. Mice were immediately euthanized when moribund or upon weight loss greater than or equal to 20% of their original body weight, as previously described [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we hypothesized we could use the M swap viruses to better understand how LACV replicates in vivo . Since La Crosse virus is the leading etiological agent of pediatric arboviral encephalitis in the United States and causes hospitalized instances of disease in humans less than 16 years old, the murine model we chose to study our LACV reassortants disease utilizes C57BL6/J neonatal mice (20). To test the neuroinvasive capacity of the M segments from our two LACV strains, we infected 6-day old mice with 50 PFU of S 1978 M 1960 L 1978 or WT LACV 1978 ( Figure 5A-C ) and 5-day old mice with 50 PFU of S 1960 M 1978 L 1960 or WT LACV 1960 ( Figure 5D-F ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that different La Crosse virus (LACV) strains exhibited differences in viral growth kinetics and pathogenesis (19) (20). However, the molecular determinants driving these phenotypes are not well-defined.…”
Section: Two Genetically Similar La Crosse Virus Strains Confer Diffe...mentioning
confidence: 99%
See 1 more Smart Citation
“…Wild-type strains of mice have been used to study the neurovirulence of a wide range of viruses, as they are susceptible to many different viral infections. Neonatal mice are acutely susceptible to many viruses and have been used extensively to study specific aspects of virus neurovirulence [ 63 , 64 , 65 , 66 ]. Their susceptibility makes them a promising model for highly sensitive neurovirulence screening.…”
Section: Animal Models For Testing Vaccine Neurovirulencementioning
confidence: 99%